Simultaneous Analysis of Unemployment Rates and Economic Growth In Java - Suharno, Suharno; Gunawan, Diah Setyorini; Utami, Rian Dwi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
ABSTRACT: This research analyzes the simultaneous anlysis between the unemployment and growth in Java Island on 2010-2022. Data were analyzed using two-stage least square. The research results are economic growth, DAU have a significant negative effect on unemployment. DAK, DBH and PMA have no effect on unemployment. Furthermore PAD, HDI have a significant positive effect on economic growth. Other, other legitimate regional income, DAK, Covid-19 dummy variables have a significant negative effect on economic growth. Unemployment and PMDN do not have a significant effect on economic growth.